Prevention of Radicalism for Alpha Generations in Raudhatul Athfal by Fatayat NU Cilacap Central Java - Novan Ardy Wiyani (AL-TAHRIR, 2019)
Abstract: This research is qualitative research aimed at describing the prevention of radicalism in alpha generation in Raudhatul Athfal (RA) by activists of Fatayat NU, Cilacap district. Radicalism is one of the threats to the millennial generation, including the generation of alpha, namely those who are studying at the level of early childhood education such as Raudhatul Athfal (RA). From the results of the study, it was revealed that radicalism had plagued teachers at Raudhatul Athfal (RA) and had an influence on the radical understanding of alpha generation in early childhood education. This was responded to by the Fatayat NU activist in Cilacap district who became a teacher at Raudhatul Athfal (RA) by making efforts to prevent radical understanding through seven ways. First, assist teachers who are influenced by radical understanding through non-formal discussion activities in a family atmosphere. Second, fortify themselves from the negative influence of radicalism by continuing to increase knowledge and religious insights from the perspective of ahlussunnah wal jamaah. Third, optimizing the implementation of religious education for the alpha generation. Fourth, optimizing the implementation of character education for the alpha generation. Fifth, introduce nationalism to the alpha generation. Sixth, creating a Raudhatul Athfal (RA) environment and a child-friendly family environment. Seventh, selective on learning materials and learning media to make sure that the learning materials and media do not have the potential to bring radical understanding.الملخص: هذا البحث يهدف إلى وصف طريقات وقاية الأجيال  من التشدد في الدين في مرحلة روضة الأطفال التي قامت بها الفتيات من منضمة نهضة العلماء في جيلاجاب (Cilacap).  مدخل هذا البحث هو البحث النوعي. و من البيانات التي حللها الباحث اكتشف أن التشدد في الدين قد تطور في أثناء المدرسين و المدرسات في مرحلة روضة الأطفال و لذلك قامت  الفتيات من نهضة العلماء بسبعة طرق لضد هذا الفهم  هي أولا الدعوة الحسنة إلى المدرسين الذين يتأثرون بهذا الفهم, ثانيا التعليم و تزويد اللكفاءة الدينية على مذهب أهل السنة و الجماعة, ثالثا تعليم الدين الإسلامي في مرحلة الطفولة, رابعا تأديب الأخلاق إلى الأجيال في مرحلة الطفولة, خامسا إحياء القومية إلى الأجيال في مرحلة الطفولة, سادسا بياء البيئة التربوية صديقة للطفل, و سابعا تقييم المنهج الدراسي و تنظيفه من الفهم التشددي.Abstrak: Penelitian ini merupakan penelitian kualitatif yang ditujukan untuk mendeskripsikan pencegahan radikalisme pada generasi alpha di Raudhatul Athfal (RA) oleh aktivis Fatayat NU kabupaten Cilacap. Radikalisme menjadi salah satu ancaman bagi generasi millenial, termasuk generasi alpha, yaitu mereka yang sedang belajar di jenjang pendidikan anak usia dini seperti pada Raudhatul Athfal (RA). Dari hasil penelitian terungkap bahwa radikalisme sudah mewabah pada guru di Raudhatul Athfal (RA) dan berpengaruh pada penanaman paham radikal bagi generasi alpha di jenjang pendidikan anak usia dini. Hal itu direspon oleh aktivis Fatayat NU kabupaten Cilacap yang menjadi guru di Raudhatul Athfal (RA) dengan melakukan upaya pencegahan terhadap paham radikal melalui tujuh cara. Pertama, melakukan pendampingan kepada para guru yang terpengaruh paham radikal melalui kegiatan diskusi secara nonformal dalam suasana yang penuh kekeluargaan. Kedua, membentengi diri dari pengaruh negatif radikalisme dengan terus meningkatkan pengetahuan dan wawasan keagamaan dalam perspektif ahlussunnah wal jamaah. Ketiga, mengoptimalkan pelaksanaan pendidikan agama bagi generasi alpha. Keempat, mengoptimalkan pelaksanaan pendidikan karakter bagi generasi alpha. Kelima, mengenalkan paham nasionalisme pada generasi alpha. Keenam, menciptakan lingkungan Raudhatul Athfal (RA) dan lingkungan keluarga yang ramah anak. Ketujuh, selektif terhadap materi-materi pembelajaran dan media pembelajaran untuk memastikan bahwa materi-materi pembelajaran dan media pembelajaran tidak berpotensi memunculkan paham radikal.